GROWTH AND YIELD RESPONSE OF MUNG BEAN PLANTS TO INTRASPECIFIC INTERACTIONS: Kacang hijau, persaingan intraspesifik, pertumbuhan dan hasil - Akhiriana, Enik; Hamawi, Mahmudah; Fitri Rahmatika, Annysa Ayu (Innofarm:Jurnal Inovasi Pertanian, 2024)
Planting more than one mung bean plant per polybag causes intraspecific interactions which can increase or decrease the production of mung bean plants (Phaseolus radiatus L.). This research aims to determine the effect of interspecific interactions on the growth and yield of mung bean plants (Phseolus radiatus L.). This research was a Completely Randomized Design (CRD) which consisted of three treatments in the form of the first treatment in the form of one plant/polybag, the second treatment in the form of two plants/polybag, and the third treatment in the form of three plants/polybag which will be repeated six times and consists of from three samples to obtain 54 experimental units. Observations made in this research were plant height (cm), number of leaves, number of pods, pod weight (grams), plant fresh weight, and plant dry weight (grams). Based on the results of the ANOVA analysis followed by the Least Significance Different (LSD) test, interspecific competition gave significantly different results for the number of pods, pod weight, fresh weight, and dry weight of plants (grams) with the best treatment of two plants/polybags